Optimization of palm oil in water nano-emulsion with curcumin using microfluidizer and response surface methodology - Revathi, Raviadaran; Davannendran, Chandran *; Liew, Huey Shin; Sivakumar, Manickam (Elsevier, 2018)
This study aims to produce and optimize palm oil-based nano-emulsion to encapsulate curcumin using microfluidizer and Response Surface Methodology (RSM). Encapsulation of curcumin is essential to overcome curcumin's poor bioavailability through the formation of nano-sized droplets in order to harvest its outstanding anti-inflammatory and anti-cancer medicinal properties. Among the parameters of concern are microfluidizer's pressure, number of cycles and surfactant concentration (Tween 80). Optimisations were performed by employing RSM. Characterisations were conducted for the droplet size, poly-dispersity index (PDI), zeta potential (ZP) and viscosity. Stable palm oil-based oil in water nano-emulsion encapsulating curcumin was achieved at a droplet size of 275.5 nm, PDI of 0.257, ZP of −36.2 and viscosity of 446 cP using microfluidizer. The optimized conditions were at 350 bar, 5 cycles and 1 wt% surfactant. Optimized microfluidizer with the aid of RSM is deemed capable to produce palm oil-based oil in water nano-emulsion encapsulating curcumin with small droplet size using low surfactant concentration and under optimum energy consumption.